Kesantunan dan Ketidaksantunan Linguistik dalam Novel Dilan: Dia Adalah Dilanku Tahun 1990 Karya Pidi Baiq - Restika Wijayanti; Atika Zahradia Maulida; I Putu Widi Rangga Aditya; Jumadi Jumadi (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study aims to describe the forms of linguistic politeness and impoliteness in the novel Dilan: He Was My Dilan in 1990 by Pidi Baiq. The research employs a descriptive qualitative approach with Leech's (1983) politeness maxims theory as the analytical framework. Data were obtained from utterances in character dialogues and narration in the novel. The findings reveal that the six politeness maxims tact, generosity, approbation, modesty, agreement, and sympathy are present in various contexts of adolescent communication in the novel. Furthermore, impoliteness appears through violations of these maxims, such as the use of harsh language, sharp sarcasm, and raised intonation. This study concludes that Dilan 1990 not only reflects adolescent social realities but also serves as a mirror of pragmatic practices in contemporary Indonesian cultural contexts.